A method to evaluate the impact of user training from the perspective of information literacy - Almeida, Fernanda Gomes; Cendón, Beatriz Valadares (Qualitative and Quantitative Methods in Libraries, 2017)
This paper reports on a qualitative research study that aimed at determining the impact of user training on the information literacy level of users of the Capes Portal of EJournals, focusing mainly on the methodological aspects of the study. Initially, the paper presents the Capes Portal of E-Journals, a digital library of scientific journals, and the actions promoted by the UFMG University Library to promote access to and use of the Portal’s information resources. A brief presentation of fundamental concepts for the study follows. The methodology was mostly qualitative and used tests, interviews and observation. Data collection was conducted in two stages: pre-instruction and postinstruction. 14 students who enrolled voluntarily in a training program offered by the university library to the UFMG community formed the sample, in the first stage - preinstruction. After the pre-instruction test, the students went through a training session. In the second stage of the research, post-instruction test and interviews, seven of the 14 students present at the initial stage participated. Data was collected through tests and observation with computer screen recording in the pre-instruction stage and, two weeks after, in the post-instruction stage. In the post-instruction stage interviews were also used. Data was obtained and analyzed based on the second standard of the ACRL Information Literacy Competency Standards for Higher Education. Results led to the conclusion that participation in training sessions can positively influence the development and achievement of information literacy competencies related to the second standard of the Information Literacy Competency Standards for Higher Education (ACRL, 2000).